Hubungan Ketersediaan Mainan Di Rumah Dengan Perkembangan Motorik Halus Anak Toddler Di Desa Widodaren Ngawi - Prasonto, Jalu Ageng; , Siti Arifah, S.Kp., M.Kes (2017)
Children in the toodler period include the second 2 years of life, at ages 1 to 3 years. In this growth there is a significant development for both gross and fine motor, then this is also a difficult time for the elderly. Toddler age is also called premises age and is a very important period to achieve growth and intellectual development optimally. Many factors are developing motor development such as stimulation of game tools. The purpose of this study was to know the sex with smooth motor development of children under five in the village of Widodaren Ngawi. The type of research design used is descriptive correlative with cross sectional approach. Proportional sampling random sampling technique in which the researchers provide equal opportunities for each element by giving an opportunity to the sample to be taken. The sample consisted of 50 respondents, namely toodler age children in Widodaren village. Data processing techniques using visual techniques used Rank spearman. Distribution of frequency at home is incomplete that is 28 respondents (50%), then complete as many as 22 respondents (44%). Distribution frequency of smooth motor development of children as many as 26 children (56%) normal, then the suspect as many as 24 children (45%) and unstestable does not exist. The results of Rank Spearman's research obtained rs value of 0.366 with a significance value of 0.002. The value of test significance (p-value) is less than 0.05 (0.002 <0.05) so that the test decision is H0 rejected as meant by the motor relationship of children under five in Widodaren Ngawi Village. Suggestions of researchers again in order to add other factors related to the ability to socialize and motor development of children under five.